2021
DOI: 10.3390/foods10081723
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Regulation of Deterioration and Preservation of Salted Kelp under Different Temperature and Salinity Conditions

Abstract: High salinity is an effective measure to preserve kelp, but salted kelp can still deteriorate after long-term preservation. In order to clarify the key conditions and microbial behavior of salted kelp preservation, 10% (S10), 20% (S20), and 30% (S30) salt concentrations were evaluated at 25 °C (T25) and 4 °C (T4). After 30 days storage, these salted kelps showed different states including rot (T25S10), softening (T25S20), and undamaged (other samples). By detecting polysaccharide lyase activity and performing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Salting is another effective measure to preserve seaweeds. Wei et al [ 3 ] evaluated the effects of salt concentrations (10, 20, 30%) at 25 and 4 °C on microbial diversity and spoilage. They found that a salinity above 20% preserved several seaweed species even at room temperature storage, and refrigeration preservation at a salinity of 10% worked as well [ 3 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Salting is another effective measure to preserve seaweeds. Wei et al [ 3 ] evaluated the effects of salt concentrations (10, 20, 30%) at 25 and 4 °C on microbial diversity and spoilage. They found that a salinity above 20% preserved several seaweed species even at room temperature storage, and refrigeration preservation at a salinity of 10% worked as well [ 3 ].…”
mentioning
confidence: 99%
“…Wei et al [ 3 ] evaluated the effects of salt concentrations (10, 20, 30%) at 25 and 4 °C on microbial diversity and spoilage. They found that a salinity above 20% preserved several seaweed species even at room temperature storage, and refrigeration preservation at a salinity of 10% worked as well [ 3 ]. However, the high salt content may limit the further use in several products and the amount of seaweed that can be used without further processing.…”
mentioning
confidence: 99%
“…Halophilic micro-organisms derived from raw kelp or pickling salt would thus thrive in salted kelp. According to our previous results, salted Laminaria are inhabited by a dense population of haloarchaea [2]. Members of the haloarchaea require high salt concentrations for growth.…”
Section: Full-textmentioning
confidence: 97%
“…Salting is another effective method for preserving high-moisture foods and can be used as a stand-alone operation or for drying vegetables and other foods [17]. High salinity is an efficient method for preserving seaweed, but salted seaweed can still degrade during long-term storage [18]. Brine solutions protect the microbiological quality of fresh foods by lowering water activity, inducing hyperosmotic shock and altering the metabolism of spoilage and harmful microbes via direct lethal actions of the chloride ion [19,20].…”
Section: Introductionmentioning
confidence: 99%